MENGELOLA PIKIRAN, PERKATAAN DAN PERBUATAN DI MASA PANDEMI COVID-19 - Ayu Veronika Somawati; Ni Wayan Wiraswastini (Jnanasidanta, 2022)
No one imagined the world would face covid-19 pandemi like it is today. This pandemi hashad a huge impact on people around the world. This is because the pandemi condition does notonly affect one aspect, but also almost all aspects of human life which makes such a big change inhuman life. Moreover, until now, no scientist has been able to predict when this pandemi will end.The purpose of writing this scientific paper is to provide solutions in dealing with the Covid-19pandemic so that a person can be more stable in the face of the Covid-19 pandemi. The methodused in this paper is a qualitative method. Collecting data in writing this scientific paper usingliterature study, namely collecting data relevant to the problems raised in this paper. The datacomes from books, journal articles and various sources, both through print and electronic media,and online media. The results of the research in this paper are that efforts to control thoughts,words and actions can be carried out through the application of Hindu religious teachings, namelyTri Kaya Parisudha (three things that must be controlled) in the midst of a pandemic, as follows:(1) In the midst of an endemic pandemic, efforts to control positive thoughts are very important.The concept of manacika parisudha can help humans to release anxiety in the midst of the chaosof the pandemic; (2) In this time of pandemic, controlling speech is very important. By notspreading hoax news, not giving false information about the covid-19 virus; and (3) Managingactions, especially in the midst of the current Covid-19 pandemic, can be done by carrying outobligations as set out by the government in its efforts to prevent the transmission of the virus fromgetting more massive. Staying focused on the obligations that should be done makes it easier forhumans to carry out these things than busy thinking about things that are outside the control ofhumans themselves.